Myeloperoxidase: indicator of cardiovascular disease in chronic kidney disease patients of tertiary care hospital of Karachi - Sabeela Noor; Faiza Alam; Fasiha Fatima; Shehryar Orakzai; Admin (Journal of the Pakistan Medical Association, 2021)
Objective: To estimate the levels of myeloperoxidase (MPO) in various stages of CKD and correlate them with inflammatory marker (CRP) and lipid profile. Methods: This cross-sectional study was conducted in the Biochemistry Department, Basic Medical Sciences Institute, Jinnah Post Graduate Medical Centre (J.P.M.C.) with collaboration of the Nephrology Department of J.P.M.C from January 2013 to September 2014. 150 participant were allocated into Group A: healthy subjects (GFR >90 ml/min/1.73m2, n=66) and Group B: CKD patients (GFR<90 ml/min/1.73m2, n=84). Serum cholesterol, triglycerides, HDL-c, CRP and myeloperoxidase were estimated. Data was presented in Mean±SD. Comparison of means within groups was performed by Mann-Whitney U test, where p-values <0.05 were considered significant. Results: With mean age of 55.64 ± 5.63 years, weight and BMI, TG, VLDL C-reactive proteins and MPO was significantly higher in in group B (p<0.001), however cholesterol and LDL-C showed no significant difference between the groups.). CRP and MPO levels demonstrated an increasing trend with decreasing GFR. Serum myeloperoxidase was found to have a significantly positive association with C-reactive protein (r = 0.710, p<0.01), cholesterol (r = 0.240, p <0.01), triglycerides (r = 0.509, p <0.01), LDL- cholesterol (r = 0.226, p <0.01) and VLDL-cholesterol (r = 0.494, p <0.01), while negative correlation with HDL- cholesterol (r= -0.370, p <0.01). Conclusion: Myeloperoxidase concentration and its relationship with lipid profile and hs-CRP in CKD patients prompts a mechanistic relationship between cardiovascular burdens in CKD patients. How ever detailed studies are required for further exploration of this link. Continuous...